Outcome of Patients with Gullain Barre syndrome at Tertiary Care Hospital in Eastern Nepal - Kafle, Dilli Ram; Shah, Surendra (Journal of Nobel Medical College, 2018)
Background: Gullain Barre syndrome is the most common cause of acute flaccid paralysis. Early diagnosis and treatment improves survival in patients with Gullain Barre Syndrome.Material and Methods: The purpose of the study was to note the common clinical features and identify predictors of outcome in Patients with Gullain Barre Syndrome. It is a prospective study which was conducted at Nobel Medical College Teaching Hospital from April 2015 to March 2016.Results: Time between onset of symptoms, presentation to hospital and admission was 5 ± 4 days. Four Patients (20%) gave history of upper respiratory tract infections and 12 (60%) had diarrhoea. Limb weakness was the most common symptom, which was documented in 20 (100%) patients. Other common symptoms were limb paresthesia, limb pain, and bladder dysfunction. Cerebrospinal Fluid protein was raised in 16(80%) patients to more than 45 mg/dl. All of our patients had CSF cell count less than 10. One (5%) patient had normal nerve conduction study initially. Eight (40%) patients had axonal (AMAN) variant of GBS, 3(15%) had AMSAN variant of GBS, while 8(40%) had demyelinating neuropathy (AIDP). The mean duration of hospital stay was7.4 ±2.7 days. Three months after hospital discharge 12(60%) patients achieved complete recovery. Eight (40%) patients still needed some support with ambulation. Predictors of worse outcome were old age, rapid progression of disease and AMSAN variant of GBS.Conclusion: Gullain Barre syndrome is an important cause of acute flaccid paralysis in children and adults. Early diagnosis is based on history of symmetrical limb weakness, CSF Findings and nerve conduction study. Majority of patients improve with supportive care while some develop respiratory failure and needs mechanical intubation. Journal of Nobel Medical College Volume 6, Number 2, Issue 11 (July-December, 2017) Page:20-24